Nano-Pd/CeO2 catalysts for hydrogen storage by reversible benzene hydrogenation/dehydrogenation reactions. (19th April 2021) - Zhou, Guilin; Li, Tao; Chen, Jiongyi; Deng, Lidan; Xie, Hongmei
Abstract: Nano-CeO2 supports, which have different structure from different preparation methods, were used to prepare nano-Pd/CeO2 catalysts. The hydrogen storage capacity of prepared nano-Pd/CeO2 catalysts were studied via vapor phase benzene hydrogenation and cyclohexane dehydrogenation reactions. Results show that the prepared Pd/CeO2 catalysts exhibit excellent benzene hydrogenation and cyclohexane dehydrogenation performances. The catalytic performance of the Pd/CeO2 catalysts is related to the dispersion of metallic Pd, hydrogen adsorption-desorption ability and structure of Pd/CeO2 catalysts and so on. And those properties are also directly affected by the morphology and mesoporous structure of the prepared nano-Pd/CeO2 catalysts that can be regulated by CeO2 support preparation methods. The synergistic effect between metal Pd, CeO2 support and their structures can effectively promote benzene hydrogenation and cyclohexane dehydrogenation, thus promoting hydrogen storage capacity. The prepared Pd/CeO2 -HT catalyst, which has high specific surface area, developed pore structure and highly dispersed metal Pd species, exhibits superior catalytic performances. And, the Pd/CeO2 -HT catalyst exhibits superior catalytic hydrogen storage performances. The benzene conversion over it at 200 °C reaches 99.5%. Whereas the cyclohexane conversion at 450 °C is 65.3%, and the H2 production capacity is 73.77 g/h. Highlights: Structure of Pd/CeO2 catalysts can be regulated by CeO2 support preparation method. Hydrogen storage between benzene and cyclohexane can be realized by Pd/CeO2 catalyst. Synergistic effect between metal Pd, CeO2 support and their structures can promote hydrogen storage. Pd/CeO2 -HT catalyst with excellent structure exhibits superior catalytic performance.